2011
DOI: 10.1007/978-1-61779-065-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Full-Length-Enriched cDNA

Abstract: A well-recognized obstacle to efficient high-throughput analysis of cDNA libraries is the differential abundance of various transcripts in any particular cell type. Decreasing the prevalence of clones representing abundant transcripts before sequencing, using cDNA normalization, may significantly increase the efficacy of random sequencing and is essential for rare gene discovery. Duplex-specific nuclease (DSN) normalization allows the generation of normalized full-length-enriched cDNA libraries to permit a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Whether finding the causative mutations or simply cataloguing the wealth of expressed genes is a priority, normalizing the RNA extract is beneficial [46,47]. In agreement with previous studies, we found that normalized samples produced the highest number of contigs but also singleton reads, which are equivalent to rare transcripts that might harbor valuable information otherwise not accessible [16,48].…”
Section: Discussionsupporting
confidence: 87%
“…Whether finding the causative mutations or simply cataloguing the wealth of expressed genes is a priority, normalizing the RNA extract is beneficial [46,47]. In agreement with previous studies, we found that normalized samples produced the highest number of contigs but also singleton reads, which are equivalent to rare transcripts that might harbor valuable information otherwise not accessible [16,48].…”
Section: Discussionsupporting
confidence: 87%
“…Such transcripts are beyond reliable detection using the types of libraries and methods we report here. Additional methods such as subcellular fractionation, cell type isolation, and library normalization or targeted enrichment will be required to reach the bottom of the transcriptome (Kapranov et al 2007;Bogdanova et al 2008).…”
Section: Spike-in Controls For Rna-seqmentioning
confidence: 99%
“…Email: endeldw @ uc.edu DNA has also been applied for many techniques using short RNA sequences [16,[18][19][20][21][22][23][24][25][26][27][28][29], but applications for long RNA targets have remained elusive.…”
Section: * Corresponding Authormentioning
confidence: 99%